THE IMPACT OF TOURISM WITH SPECIAL REFERENCE TO DISTRICT NAINITAL - Rastogi, Amarnath; Pushpa Pant (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Travel has always been an important part of human life. Tourism development brings socio-economic benefits like income generation and job creation but also poses challenges such as environmental degradation and cultural commodification. This paper reviews the impacts of tourism growth, highlighting its positive contributions to local livelihoods alongside concerns over problems arising from it. This study seeks to assess the effects of tourism in Nainital District, also known as the 'Lake City of India' and a popular tourist destination. The major focus is on Nainital town and its surrounding tourist attractions. Findings are based on both primary and secondary data sources.